Quality And Stability Of Duck Sausages - ., Muthia Dewi (2012)
A study on quality physicochemical, textural, sensory attributes and stability of duck sausage has been conducted with respect to the following these objectives: 1) to study the effects of different flours (tapioca, wheat, sago and potato) on duck sausage quality; 2) to evaluate the effects of combination of tapioca flour or sago flour and egg white powder (EWP) in duck sausage making; and 3) to compare the effects of adding garlic (fresh and powder) on duck sausage quality during refrigerated storage. In Experiment 1, the production of duck sausage with different type of flours (tapioca, wheat, sago and, potato) showed significant difference (P > 0.05) on protein, fat, ash and carbohydrate contents.